PENYULUHAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SD NEGERI 4 KRONGGEN MELALUI PROGRAM KKN - Nanda Febriana; Noor Alis Setiyadi (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2026)
Students at SD Negeri 4 Kronggen showed limited awareness regarding Clean and Healthy Living Behavior (PHBS). This community service activity aimed to improve students' knowledge through interactive health education. Activities included healthy exerc ise, educational sessions, handwashing demonstrations, question-and-answer sessions, and coloring activities. The program improved students' understanding and awareness of healthy behaviors both at school and at home.